Beyond general food craving: sex differences in food-specific craving identified using item response theory - Jun, Daiil; Joo, Sean; Fazzino, Tera L. (Frontiers in Psychology, 2025)
BackgroundFood craving plays a significant role in food choice and excess energy intake. While prior research has predominantly examined food craving as a general construct (e.g., craving for foods overall), this approach may obscure important variability in craving for specific foods. The current study aimed to address this limitation by examining craving for specific foods (food-item level) and examining differences across sex in food item craving, while controlling for overall food craving.MethodsThe sample (N = 583) was collected via crowdsourcing. The Food Craving Inventory was used to assess craving for 28 food items. Using item response theory (IRT), a partial credit model was employed to investigate which food item was easier or more commonly craved, while holding overall food craving level constant across participants. Differential item functioning (DIF) analysis identified sex differences in craving for specific food items, with effect sizes calculated to interpret the magnitude of DIF.ResultsThe partial credit model revealed that pizza and chocolate were the easiest or most commonly craved, while gravy and cornbread were the most difficult to crave. DIF analysis suggested that savory items were more difficult (or less commonly) craved among females with medium effect sizes (i.e., Cohen's D) ranging from 0.53 to 0.80, whereas sweets were more difficult for males to crave, with effect sizes ranging from 0.42 to 0.49.ConclusionFindings indicated that food craving may vary depending on specific foods and sex.